Let x ≥ y be real numbers such that:
( 2 x + 2 y − 1 ) ( x + y ) − 6 x y = − 2 1
The sum of all possible different values of x is b a , with a and b are coprime positive integers. Compute a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Expand:
2 y 2 − y ( 2 x + 1 ) + 2 x 2 − x + 1 / 2 = 0
Solve after y :
y = 4 1 ( 2 x + 1 ± 1 2 x − 1 2 x 2 − 3 ) = 4 1 ( 2 x + 1 ± 3 − ( 2 x − 1 ) 2 )
Since we're interested in real solutions 2 x − 1 must be zero, hence x = 1 / 2
Problem Loading...
Note Loading...
Set Loading...
( 2 x + 2 y − 1 ) ( x + y ) 2 x 2 − 2 x y + 2 y 2 − x − y + 2 1 4 x 2 − 4 x y + 4 y 2 − 2 x − 2 y + 1 ( x 2 + 2 x y + y 2 − 2 x − 2 y + 1 ) + ( 3 x 2 − 6 x y + 3 y 2 ) ( x + y − 1 ) 2 + 3 ( x − y ) 2 = − 2 1 = 0 = 0 = 0 = 0
Since x and y are real numbers, the only possible solution needs to fulfill the following equations:
x + y − 1 = 0 and x − y = 0
Adding both equations results in
x = 2 1 and y = 2 1 .
Therefore
a = 1 and b = 2 ⇒ a + b = 3 .